A TOPSIS Extension Framework for Re-Conceptualizing Sustainability Measurement. - Afful-Dadzie, A.; Afful-Dadzie, E.; Turkson, C. (Emerald Publishing Limited, 2016)
Purpose – The purpose of this paper is to propose a sustainability measurement and scoring system for assessing the efforts of organizations at meeting sustainability targets. Using technique for order preference by similarity to ideal solution (TOPSIS) as the basic framework, the proposed method incorporates all three sustainability dimensions – economic, environmental and social – to establish a threshold below which an organization is considered to have failed a sustainability test. In Addition, an introduction of a time-independent threshold enables a clearer comparison of performance of organizations over time. The proposed method includes plots for visualizing the sustainability performance of organizations under review. Design/methodology/approach – The proposed method first assigns target values to a hypothetical organization. TOPSIS is then used to generate composite scores in which the score of the hypothetical organization is set as the threshold below which organizations are deemed to have failed a sustainability test. Using the square of the closeness coefficient of TOPSIS, the final composite score is decomposed into three components to reflect the contribution of the three dimensions of sustainability to serve as a guide to determining which dimension to focus on for improvement. A relative comparison score is then proposed to track the performance of organizations over time. Findings – The proposed method with its ability to set a threshold is able to determine organizations that have passed a sustainability test from those that have failed. The tracking of organizational performance over time also serves to highlight progress being made by organizations to meet an agreed sustainability target. Results from the application of the proposed method for evaluating sustainability of banks under the three dimensions of sustainability highlight its practical applicability. The proposed method can also be applied to a wide range of comparison problems including make-or-by decisions and award selection. Practical implications – As most industries and organizations become conscious of the pressure to adopt sustainable practices, the proposed measuring system would help identify those that are meeting sustainability targets as well as to track their progress over time. Originality/value – Most sustainability measurement indicators rarely have thresholds to determine whether an organization has met or failed to meet a sustainability test other than ranking them from top to bottom. The proposed method provides a threshold as well as a procedure for tracking the sustainability performance of organizations over time.
Keywords: Decision making; TOPSIS; Multi-criteria decision making; Threshold; Sustainability measurement